FORMALISASI SYARIAH = DOMINASI NALAR NEGARA: Studi atas Dominasi Nalar “State” Terhadap Islam Pasca Reformasi di Indonesia - M. Sholihin (Millah: Journal of Religious Studies, 2011)
The paper aim to analyze the logic state, that applied for Islam in the post-reform era in Indonesia. And the formalization of sharia in conjunction with the state of reason, could be focussing of analysis. By using the interpretive approach, supported by the theory of "state"; Bourdieu's theory of symbolic power, and the theory of tyranny Muhammad Shahrur, the phenomenon of formalization of sharia in Indonesia are explored more widely